Hybridization and introgression between toads with different sex chromosome systems. Issue 5 (1st October 2020) - Dufresnes, Christophe; Litvinchuk, Spartak N; Rozenblut-Kościsty, Beata; Rodrigues, Nicolas; Perrin, Nicolas; Crochet, Pierre-André; Jeffries, Daniel L
Abstract: The growing interest in the lability of sex determination in non-model vertebrates such as amphibians and fishes has revealed high rates of sex chromosome turnovers among closely related species of the same clade. Can such lineages hybridize and admix with different sex-determining systems, or could the changes have precipitated their speciation? We addressed these questions in incipient species of toads (Bufonidae), where we identified a heterogametic transition and characterized their hybrid zone with genome-wide markers (RADseq). Adult and sibship data confirmed that the common toad B. bufo is female heterogametic (ZW), while its sister species the spined toad B. spinosus is male heterogametic (XY). Analysis of a fine scale transect across their parapatric ranges in southeastern France unveiled a narrow tension zone (∼10 km), with asymmetric mitochondrial and nuclear admixture over hundreds of kilometers southward and northward, respectively. The geographic extent of introgression is consistent with an expansion of B. spinosus across B. bufo 's former ranges in Mediterranean France, as also suggested by species distribution models. However, widespread cyto-nuclear discordances ( B. spinosus backrosses carrying B. bufo mtDNA) run against predictions from the dominance effects of Haldane's rule, perhaps because Y and W heterogametologs are not degenerated. Common and spined toads can thus successfully cross-breed despite fundamental differences in their sex determination mechanisms, but remain partially separated by reproductive barriers. Whether and how the interactions of their XY and ZW genes contribute to these barriers shall provide novel insights on the debated role of labile sex chromosomes in speciation.